PROFITABILITAS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL MODERASI STRUKTUR MODAL - Angelia, Maria Natasya; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2025)
This research aims to determine the impact of profitability and institutional ownership also capital structure as moderating variable on property & real estate company’s value listed on the Indonesia Stock Exchange during 2019-2021. Sample was selected using purposive sampling method and the valid data was 77 from 31 companies. Data processing techniques using moderate regression analysis which helped by SPSS software (Statistical Product and Service Solution) for Windows version 26 and Microsoft Office Excel. The results of this study indicate that profitability has a positive effect on firm value, institutional ownership has no effect on firm value, capital structure is able to moderate the effect of profitability on firm value, meanwhile capital structure is unable to moderate the effect of institutional ownership on firm value. The implications on this research are institutional ownership is expected to play a role more effective, it is also necessary to increase the level of profitability and capital structure in order to provide a good signal for investors that can increasing the firm value.